Absence of nosocomial influenza and respiratory syncytial virus infection in the coronavirus disease 2019 (COVID-19) era: Implication of universal masking in hospitals. (17th February 2021) - Wong, Shuk-Ching; Lam, Germaine Kit-Ming; AuYeung, Christine Ho-Yan; Chan, Veronica Wing-Man; Wong, Newton Lau-Dan; So, Simon Yung-Chun; Chen, Jonathan Hon-Kwan; Hung, Ivan Fan-Ngai; Chan, Jasper Fuk-Woo; Yuen, Kwok-Yung; Cheng, Vincent Chi-Chung
Abstract: Universal masking for healthcare workers and patients in hospitals was adopted to combat coronavirus disease 2019 (COVID-19), with compliance rates of 100% and 75.9%, respectively. Zero rates of nosocomial influenza A, influenza B, and respiratory syncytial virus infection were achieved from February to April 2020, which was significantly lower than the corresponding months in 2017–2019.